Apophyseal ring fracture associated with two levels extruded disc herniation: case report and review of the literature - Alvarenga, José Alexandre Lopes da Silva (2014)
Apophyseal ring fractures are rare injuries that may be associated with lumbar disc herniation in young patients. We report a unique case in the literature of a 15-year-old male patient who played football and was admitted at our service complaining of sciatica radiating into the left leg. An apophysial ring injury of L5 vertebral body was observed. This injury caused two extruded disc herniation in adjacent levels. Surgical procedure was indicated after failure of conservative treatment.